The Role of Adenosine Receptors in Psychostimulant Addiction - Ballesteros-Yáñez, Inmaculada; Castillo, Carlos A.; Merighi, Stefania; Gessi, Stefania (Frontiers in Pharmacology, 2018)
Adenosine receptors are a family of G-protein coupled receptors, comprised of four members, named A1, A2A, A2B and A3 receptors, found widely distributed in almost all human body tissues and organs. To date, they are known to participate in a large variety of physiopathological responses, which include vasodilation, pain and inflammation. In particular, in the central nervous system (CNS), adenosine acts as a neuromodulator, exerting different functions depending on the type of adenosine receptor and consequent cellular signaling involved. In terms of molecular pathways and second messengers involved, A1 and A3 receptors inhibit adenylyl cyclase, through Gi/o proteins, while A2A and A2B receptors stimulate it through Gs proteins. In the CNS, A1 receptors are widely distributed in the cortex, hippocampus and cerebellum, A2A receptors are localized mainly in the striatum and olfactory bulb, while A2B and A3 receptors are found at low levels of expression. In addition, adenosine receptors are able to form heteromers, both among themselves (e.g. A1/A2A), as well as with other subtypes (e.g. A2A/ D2), opening a whole range of possibilities in the field of the pharmacology of adenosine receptors. Nowadays, we know that adenosine, by acting on adenosine A1 and A2A receptors, is known to antagonistically modulate dopaminergic neurotransmission and therefore reward systems, being A1 receptors colocalized in heteromeric complexes with D1 receptors, and A2A receptors with D2 receptors. This review documents the present state of knowledge of the contribution of adenosine receptors, particularly A1 and A2A, to psychostimulants-mediated effects, including locomotor activity, discrimination, seeking and reward, and discuss their therapeutic relevance to psychostimulant addiction. Studies presented in this review reinforce the potential of A1 agonists as an effective strategy to counteract psychostimulant-induced effects. Furthermore, different experimental data support the hypothesis that A2A/D2 heterodimers are partly responsible for the psychomotor and reinforcing effects of psychostimulant drugs, such as cocaine and amphetamine, and the stimulation of A2A receptor is proposed as a potential therapeutic target for the treatment of drug addiction. The overall analysis of presented data provide evidence that excitatory modulation of A1 and A2A receptors constitute promising tools to counteract psychostimulants addiction.